A control-based middleware framework for quality-of-service adaptations. - Baochun Li (IEEE Journal on selected areas in communications)
In heterogeneous environments with performance variations present, multiple applications compete for and share a limited amount of system resources and suffer from variations in resource availability. These complex applications are desired to adapt themselves and to adjust their resource demands dynamically. On one hand, current adaptation mechanisms built within an application cannot preserve global properties such as fairness; on the other hand, adaptive resource management mechanisms built within the operating system are not aware of data semantics in the application. In this paper, we present a novel middleware control framework to enhance the effectiveness of quality-of-service (QoS) adaptation decisions by dynamic control and reconfiguration of internal parameters and functionalities of a distributed multimedia application. Our objective is to satisfy both system-wide properties (such as fairness among concurrent applications) and application-specific requirements (such as preserving the critical performance criteria). The framework is modeled by the task control model and the fuzzy control model, based on rigorous results from the control theory, and verified by the controllability and adaptivity of a distributed visual tracking application. The results show validation of the framework, i.e., critical application quality parameters can be preserved via controlled adaptation